Reconstructing Stakeholder Trust in an Existential Crisis: A Conceptual Study of PT Sritex's Crisis Communication Management Post-Bankruptcy Decision - Nadia Pipit Safitri; Alfia Risma Kinanti; Julia Ari Safira; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
The global textile industry faced significant structural upheavals in the 2024–2025 period, placing strategic entities like PT Sri Rejeki Isman Tbk (Sritex) under extreme existential threats. This conceptual article examines the anomaly of corporate resilience where a formal bankruptcy status is met with massive social and political support rather than reputational collapse. Using a qualitative-descriptive approach, the study synthesizes Situational Crisis Communication Theory (SCCT) and Image Repair Theory with the realities of economic nationalism in developing economies. The analysis reveals that the integration of a "national interest" narrative and symbolic communication tactics—such as the "humanization" of the industrial giant through its workforce—functions as a powerful "human shield" against legal liquidation. The findings introduce the "Survival-Driven PR" model, which integrates legal defense, social support, and political lobbying as a cohesive defense mechanism. This research contributes to crisis management literature by redefining Public Relations as a strategic diplomatic instrument capable of converting social modality into political bargaining power. Ultimately, the study concludes that for "Too Big to Fail" entities, operational legitimacy is maintained by aligning corporate survival with national industrial sovereignty and the collective welfare of the labor force.